2017
DOI: 10.1007/s12035-017-0683-3
|View full text |Cite
|
Sign up to set email alerts
|

Double-Injected Human Stem Cells Enhance Rehabilitation in TBI Mice Via Modulation of Survival and Inflammation

Abstract: Traumatic brain injury (TBI), a complicated form of brain damage, is a major cause of mortality in adults. Following mechanical and structural primary insults, a battery of secondary insults, including neurotransmitter-mediated cytotoxicity, dysregulation of calcium and macromolecule homeostasis, and increased oxidative stress, exacerbate brain injury and functional deficits. Although stem cell therapy is considered to be an alternative treatment for brain injuries, such as TBI and stroke, many obstacles remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
(48 reference statements)
0
10
0
1
Order By: Relevance
“…In another study, exosome injection of MSCs after 15 minutes from the TBI could inhibit the in ammation by disturbing the injury cycle [41]. On the other hand, other studies stated that early administration of SC could not be effective due to the tissue in ammation, and delayed administration or repeating the dose may result in more effective outcomes [2,42]. This study investigated repeating the injection of OMSCs in 1 and 24 hours after the injury.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In another study, exosome injection of MSCs after 15 minutes from the TBI could inhibit the in ammation by disturbing the injury cycle [41]. On the other hand, other studies stated that early administration of SC could not be effective due to the tissue in ammation, and delayed administration or repeating the dose may result in more effective outcomes [2,42]. This study investigated repeating the injection of OMSCs in 1 and 24 hours after the injury.…”
Section: Discussionmentioning
confidence: 97%
“…Traumatic brain injury (TBI) is one of the major causes of death and disability worldwide [1,2]. Despite the effective therapeutic options available, TBI treatment remains a challenge for scientists and physicians [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both central ( 49 60 ) and systemic ( 60 75 ) administration of MSCs 24 h post-TBI have resulted in early and persistent improvements of functional and structural outcomes. It was recently shown that a double systemic infusion of MSC (at 4 and 24 h) post-TBI was more effective than a single dose at 24 h ( 76 ). The authors showed 4 and 24 h post-TBI peaks of IL1β, TNFα, and IFNγ, suggesting that a shorter lag time between TBI and treatment may be important to counteract early pro-inflammatory changes.…”
Section: Window Of Opportunity For Pharmacological Neuroprotection Inmentioning
confidence: 99%
“…Показано, что активация иммунного ответа достигает максимума между 5 и 7 днями по-МЕЖДУНАРОДНЫЙ ЖУРНАЛ ПРИКЛАДНЫХ И ФУНДАМЕНТАЛЬНЫХ ИССЛЕДОВАНИЙ № 12, 2017 99  БИОЛОГИЧЕСКИЕ НАУКИ  сле ЧМТ и остается повышенной в течение 2 недель, что дает временной интервал для терапевтического вмешательства [1]. Нако-нец, ЧМТ приводит к апоптозу и ишемии ткани головного мозга и функциональному дефициту [2].…”
Section: Abstract: Traumatic Brain Injury Biodegradable Scaffold Peunclassified